Differential metabolic pathways underlie THC- and CBD-mediated inhibition of B-cell activation in both young and aged mice - Yekhtin, Zhanna; Petukhov, Dmytro; Khuja, Iman; Kogan, Natalya M.; Or, Reuven; Almogi-Hazan, Osnat (Frontiers in Immunology, 2025)
ObjectiveB lymphocytes play a crucial role in immunity but also contribute to the pathogenesis of various diseases. Cannabis plants produce numerous biologically active compounds, including cannabinoids. The two most studied phytocannabinoids are Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD). These cannabinoids exert diverse and potent biological effects primarily through the endocannabinoid system (ECS), which also plays a key role in mature B-cell function. Both the immune system and the ECS undergo age-related changes that lead to a clinically significant decline in function.MethodsThis study compares the effects of THC and CBD on B-cell activity in young and aged mice. Murine B lymphocytes were activated using lipopolysaccharide (LPS) and interleukin-4 (IL-4), and the impact of cannabinoid treatments was assessed in terms of cell phenotype, proliferation, antibody secretion, tumor necrosis factor-alpha (TNFα) secretion, extracellular signal-regulated kinase (ERK) phosphorylation, and the cellular metabolome.ResultsBoth THC and CBD exhibited dose-dependent inhibitory effects on B-cell activation in young and aged mice. However, we show here, for the first time, that the treatments induce distinct metabolic profiles. Although some metabolites, such as glucose-6-phosphate, pentose phosphate pathway (PPP) and nucleotide metabolites, were reduced by both cannabinoids, THC selectively reduced the levels of a distinct set of amino acids, while only CBD increased the levels of Citrulline and Allantoin. Additionally, the effects of THC and CBD differed between young and aged B cells, suggesting that age-related changes in the ECS may influence cannabinoid sensitivity.ConclusionsThese findings provide insights into the distinct mechanisms by which THC and CBD regulate immune activation and may open the door for investigating the mechanisms behind cannabinoids effects on the immune system. They also highlight the need for further research into phytocannabinoid-based therapies, particularly in age-specific contexts. Given the immunoregulatory properties of cannabinoids, especially CBD, tailored therapeutic strategies may enhance their clinical applications